Synthesis of a novel biodegradable curing agent modified by castor oil for polyacrylate adhesive applications. Issue 12 (19th January 2023) - Cai, Yangben; Chen, Guofei; Yu, Zhujun; Lu, Jianxian; Fang, Xingzhong
Abstract: A novel functional carbamate oligomer with high curing activity was prepared by addition polymerization using diisocyanate and castor oil (CO) and used as curing agent for polyacrylate adhesive. The influence factors of such modified castor oil (mCO) preparation, including monomer type, NCO/OH group mole ratio, reaction temperature and time, were explored. When the CO was reacted with hexamethylene diisocyanate among the NCO/OH group mole ratio of 0.56–0.75 at 75°C for 4 h, the NCO value of mCO could be in the range between 0.10 and 0.20 mmol/g. At this point, the peel adhesion and the tack of the adhesive with mCO in the mass ratio of 1/1 can be above 2.3 N/cm and 23#, respectively. In addition, the influence of rosin resin content, polyacrylate content, and the active equivalent of mCO on the properties of adhesive tape was studied in detail. When the pressure sensitive adhesive is prepared by 50% polyacrylate, 25% mCO and 25% rosin resin, the peel adhesion and the tack can reach 4.63 N/cm and 23#. The relative biodegradation rate of cured adhesive with 25% of mCO and 25% of rosin resin is 47.56% after 45 days, with an increase of 80.95% compared to that of pure adhesive. The highly biodegradable mCO endows the adhesive tape with better mechanical property and biodegradability, thus making it a promising adhesive tape for packing applications. Abstract : Every component in the castor oil modified polyacrylate tape can be degraded by microorganisms and turns into carbon dioxide and water via hydrolysis, terminal oxidation biodegradation (TOB) or subterminal oxidation biodegradation (SOB), which contributes to good biodegradability.